PENGARUH PENGGUNAAN MEDIA BAGAN TANGGA SATUAN PANJANG TERHADAP MOTIVASI BELAJAR DAN IMPLIKASINYA TERHADAP HASIL BELAJAR SISWA (Studi Quasi Eksperimen Pada Siswa Kelas IV Mata Pelajaran Matematika di SD Negeri 1 Winduhaji) - Novi Satria Pradja; Husna Latif (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2018)
Abstract: In this study used to find out the results of the posttest in the class that uses the learning media ladder chart with classes that do not use the learning media unit ladder chart and to know the differences in student learning outcomes in classes that use ladder chart learning media with increased student learning outcomes in class who do not use the media learning charts and student learning assistance in the fourth grade of SDN 1 Winduhaji Mathematics. The method used in this study is nonequivalent control group design design. The subject of this study was to take two classes, namely class A consisting of 33 students as a control class and class B consisting of 34 students as an experimental class. The research instrument used multiple choice questions and learning motivation questionnaires. Than, an analysis of instrument and data analysis is carried out. Data analysis in the control class and experimental class using SPSS version 22. Analysis of the data in the experimental class and control class showed that the t test value was 0.000 0.05. The results showed that the learning media used to study and learn the learning outcomes of students who use learning media that cannot use the learning media ladder unit length chart. From these data it can be extended that the learning charts of the ladder chart are very long towards learning and student learning outcomes and can be used as an alternative learning media for teachers in increasing motivation and learning outcomes.Keywords: Learning Media Long Unit Ladder Chart, Learning Motivation and Learning Outcomes.